CONVERSATION ANALYSIS: TURN-TAKING MECHANISM AND POWER RELATION IJ CLASSROOM SETTING - Candrika Citra Sari (University of Muhammadiyah Malang, 2020)
Institutional conversation in the classroom has been known to be fully controlled by the teacher in order to achieve specific goals of the teaching and learning process. This study aims at finding out how teachers manage the flow of classroom interaction, how students may possibly take the floor and issue about power and hierarchy between teacher-students in teacher-fronted whole classroom interaction. The result is expected to give an overview or a reflection on how teachers encourage learning to happen by the way they use their power to manage the turn-taking mechanism in whole-class interaction. The data is in the form of unscripted classroom interaction in the field of language from YouTube. Specifically, the analysis is focussed on analyzing the turn-taking rules in a whole class interaction using Conversation Analysis (CA). The gesture is also one means of communication that accompanied verbal communication, and therefore to enrich the data, the gestures of the participants are also taken into consideration. This study found that teacher and students' turn is asymmetrical. However, the teacher possesses no absolute power in terms of controlling the turn-taking as students appeared to overlap the teacher’s talk to take the turn and try to perform an unfocalized effort to nominate themselves as the first speaker using gestures. The content of teachers’ TCU indicates that the teacher tries to stimulate the students’ critical thinking by posting an open-ended question, and evaluates and responds to students’ answers by using a follow-up question.